Dangerous Bodies New Global Perspectives on Fashion and Transgression - Mahawatte, Royce; Willson, Jacki (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"Dangerous Bodies is an excellent interdisciplinary collection focusing on issues of transgression and the fashioned body. The chapters explore the role of sartorial politics in challenging various forms of hegemony and authority. How can dress challenge oppression? How does it become a point of resistance? How can it create spaces of belonging? These are some of the key issues Mahawatte and Willson's book deftly responds to." - Rohit K. Dasgupta, Senior Lecturer, University of Glasgow, UK This edited book brings together new perspectives on fashion, the body, and politics. The intention of this collection is to explore the cultural intersection between bodies, fashion, and transgression, often in the most unlikely of locations. Bodies are political players in culture and the authors gathered here ask a range of pressing questions. What role do fashioned bodies play in resistance, in meeting governmental boundaries or institutional power? Arguably, fashion is an aspect of modern warfare and style can defend and attack in cultural space. So, how do fashioned bodies occupy the grey area between social control and the resistance to power? This book is interdisciplinary and international, with contributors situated within a broad range of disciplines including Art History and Critical Practice, Cultural Studies, Fashion Critical Studies, Film and Literary Studies, Performance Studies, Politics and International Studies, Sociology, Gender, Queer, LGBTI, and Critical Race Studies. Royce Mahawatte is Senior Lecturer in Cultural Studies at Central Saint Martins, University of the Arts London and a member of the faculty at NYU London, UK. He is the author of George Eliot and the Gothic Novel (2013) and has published journal articles in Women's Writing and Sexualities, and the chapters 'Fashion and Adornment' in A Cultural History of Hair (2018) and 'The Sad Fortunes of 'Stylish Things': George Eliot and the Languages of Fashion' in Communicating Transcultural Fashion Narratives (2018). He is also Director of Research at the think tank Fashion Roundtable, and during 2020-2021 was a Heinz Heinen Fellow at the Centre for Dependency and Slavery Studies, University of Bonn, Germany. Jacki Willson is Associate Professor in Performance and Gender in the School of Performance and Cultural Industries at the University of Leeds, UK. She has published two monographs - The Happy Stripper: Pleasure and Politics of the New Burlesque (2008) and Being Gorgeous: Feminism, Sexuality and the Pleasures of the Visual (2015) - and one edited collection, Revisiting the Gaze: The Fashioned Body and the Politics of Looking (2020). She is Principal Investigator of a three-year AHRC-funded project, Fabulous Femininities: Extravagant Costume and Transformative Thresholds (2020-).
1. Introduction: Fashion, Bodies, Transgression, Royce Mahawatte and Jacki Willson -- Section 1, Dangerous Surfaces -- 2. Contagion and the Excess of Gender, Race, and Commodity, Nigel Lezama, Cardi B's Nails -- 3. "Let me be your Stimmy Toy": Fashioning Disability, Cripping Fashion, Jana Melkumova-Reynolds -- 4. "Under False Colors": Nineteenth-Century Masquerading Laws and Black Disabled Transgender Embodiment in Post-Civil War Memphis, Ardel Haefele-Thomas -- 5. "One Club Fits All": Male Embodiment in an Age of Homonormativity, Royce Mahawatte -- Section 2, Fashion and Spatial Transgression -- 6. The Politicisation of Palestinian Embroidery since 1948, Rachel Dedman -- 7. Polish 'Black Protests': political dress and the politics of fashion, Alicja Raciniewska -- 8. Performative Elegance: The Windrush Generation, Fashion and the Politics of Respectability, Telecia Kirkland -- Section 3 Embodiment and Abstract Boundaries -- 9. Non-Norm-(Hard)-Core: Hood by Air's Porn Archive, Francis Summers -- 10. Consuming (beyond plain) Vanilla: 'straight' coupledom and illicit performativities on popular culture TV show Love Island, Jacki Willson -- 11. Terrifying Beauty - Theatrical Self-Performance in Leonor Fini's Art and Life, Andrea Kollnitz.
Keywords: Motion pictures; Identity politics; Performing arts; Theater; Gender and Culture; Audio-Visual Culture; Politics and Gender; Theatre and Performance Arts